Correlation between knowledge, attitude, practice toward anxiety, and perception of the need for mental health services in Bali communities during the COVID-19 pandemic - Putu Satyakumara Upadhana; I Gede Gita Sastrawan; I Gusti Agung Ayu Chintya Cahyarini; Ni Putu Gita Raditya Sanjiwani; Ida Ayu Kanaka Puspita; Wayan Citra Wulan Sucipta Putri; Ida Aju Kusuma Wardani (Indoscholar, 2022)
Background: The level of knowledge, attitudes, and practices of a person in dealing with the COVID-19 pandemic can be a factor that influences the emergence of anxiety disorders. The study aims to determine the correlation between knowledge, attitude, practice toward anxiety, and perception of the need for mental health services in Bali communities during the COVID-19 pandemic. Methods: This study was a cross-sectional observational analytical study with a consecutive sampling method. An online questionnaire was distributed in all provinces by the enumerator from 1 November to 30 November 2020. The inclusion criteria are respondents that lived in Bali and were aged between 18 to 65 years old. Results: There were 356 respondents included in this study. Most of them were female (n = 227, 63.8%), and not married (n = 251, 70.5%), with a median age of 25 years old (18-64 years old). There was a significant correlation between attitude and perception of the need for mental health service (p = 0.028, R = 0.177) and anxiety of the respondent (p = 0.004, R = 0.151). Also, the correlation between practice and perception of the need for mental health (p = 0.039, R = 0.109) and anxiety with the perception of the need for mental health (p = 0.039, R = 0.109) were found to be statistically significant. Conclusion: There is a correlation between knowledge, attitude, practice toward anxiety, and perception of the need for mental health services in Bali communities during the COVID-19 pandemic.